Quitting : a life strategy : the myth of perseverance--and how the new science of giving up can set you free - Keller, Julia (Balance, Hachette Book Group, 2023)
"Grit isn't always great. Perseverance doesn't always pay off. In Quitting: A Life Strategy, Pulitzer prize-winning journalist Julia Keller dives into "the neuroscience of nope," and the cultural messaging that drives our reluctance to throw in the towel, to dismantle the myth of perseverance once and for all. Combining reportage from the front lines of scientific research, pop culture, with conversations with people who have made profound change in their own lives and "Permission Slips" to guide readers in their own embrace of quitting, Keller gives readers the rationale and confidence they need to pull the plug and shape their own lives without fear-at work, at home, in our relationships, and beyond"--